Analisis Pengaruh Faktor Fundamental dan Makroekonomi terhadap Harga Saham Subsektor Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia periode tahun 2020-2024 dengan Inflasi sebagai Variabel Moderasi - Dina Destia Laila Safitri; Pradana Jati Kusuma; Suhita Whini Setyahuni; Rudi Kurniawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study examines the effect of fundamental factors (ROA, DER, CR, PBV, EPS) and macroeconomic factors (exchange rates, interest rates) on stock prices of food and beverage companies listed on the Indonesia Stock Exchange during 2020–2024, with inflation as a moderating variable. Using a quantitative approach and secondary data from financial statements and macroeconomic sources, the sample comprises 20 companies (100 observations). Results show that EPS and PBV have a positive and significant effect on stock prices, while ROA, DER, CR, exchange rates, and interest rates are not significant. Inflation moderates the relationship between ROA and PBV with stock prices, but not for other variables. The findings indicate that profitability and market valuation are the main factors considered by investors, while inflation plays a selective role.